2013
DOI: 10.1039/c3sc50369k
|View full text |Cite
|
Sign up to set email alerts
|

A near-infrared ratiometric fluorescent probe for rapid and highly sensitive imaging of endogenous hydrogen sulfide in living cells

Abstract: We describe the design and synthesis of a cyanine-based near-infrared ratiometric fluorescent probe, HS-Cy, for H 2 S detection, which features rapid response, high sensitivity, and mitochondria targeting. After a rapid quenching at 780 nm by initial nucleophilic addition on the aldehyde group, HS-Cy experienced a polymethine p-electron conjugation modulation triggered by a second nucleophilic addition on the ester, releasing the cyanine fluorophore which underwent tautomerism from enol form to ketone form. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
148
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 325 publications
(155 citation statements)
references
References 52 publications
4
148
0
3
Order By: Relevance
“…1, the linear relationships with the quite low detection limits of 2.7 nM and 6.9 nM were achieved respectively for ClO -and H 2 S. Undoubtedly, the detection limit for H 2 S with BNBD was comparable to the detection limit provided by the chemical probe reported as the most sensitive 34 , so was the detection limits for ClO -46 . We attribute the high detection sensitivity to both the large (150 fold) Off-On-Off switch of fluorescence and the strong oxidizing power of nitro group and ClO -under the acidic condition.…”
Section: Quantifications Of Clo -/ H 2 S and Analytical Strategymentioning
confidence: 67%
See 1 more Smart Citation
“…1, the linear relationships with the quite low detection limits of 2.7 nM and 6.9 nM were achieved respectively for ClO -and H 2 S. Undoubtedly, the detection limit for H 2 S with BNBD was comparable to the detection limit provided by the chemical probe reported as the most sensitive 34 , so was the detection limits for ClO -46 . We attribute the high detection sensitivity to both the large (150 fold) Off-On-Off switch of fluorescence and the strong oxidizing power of nitro group and ClO -under the acidic condition.…”
Section: Quantifications Of Clo -/ H 2 S and Analytical Strategymentioning
confidence: 67%
“…On the other hand, in situ determination of endogenous H 2 S in tissue is still a challenge, because it requires the rapid and sensitive response. It was found that sensing H 2 S through the nucleophilic attack or CuS precipitation needed relatively long time 34 . Though azide in fluorophore could rapidly report the trace level of H 2 S within minutes, it might be protonated in the highly acidic environment.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, fluorescence-based systems for H 2 S detection have been proposed as selective probes for biological applications. [9][10][11][12][13][14][15][16][17][18][19][20] These probes can detect H 2 S in aqueous solution with high sensitivity and selectivity. Existing fluorescencebased probes implemented so far have been subdivided into four different categories (depending on the reaction mechanism by which analyte recognition occurs): [1,19] (i) azide-toamine reduction; [12,[21][22][23][24][25][26][27] (ii) nucleophilic addition; [28][29][30][31] (iii) copper displacement; [32][33][34][35][36] and (iv) nitro-to-amine reduction.…”
Section: Introductionmentioning
confidence: 99%
“…2) the interruption of a large conjugate system by H 2 S addition can produce ratiometric probes with relatively large Stokes shifts. However, this method can only turn-on the signal at the shorter emission wavelength [25][26][27] . If we employ FRET effect as an alternative strategy for ratiometric H 2 S probes, 1) the turn-on signal can be at longer emission wavelength (FRET acceptor emission) and 2) the FRET pairs could be chosen flexibly for facile control of two emission wavelengths at specific wavelength ranges.…”
Section: Discussionmentioning
confidence: 99%
“…The intensity-based fluorescence probes may suffer from multiple factors to influence the accurate analysis of H 2 S production and regulation in living cells. However, the ratiometric fluorescence probes provide built-in correction for environmental effects to improve the accuracy of bioimaging analysis [22][23][24][25][26][27] . The reported sulfide ratiometric probes are mainly based on two strategies: 1) a tuneable electronic system, after reaction with H 2 S, results in a spectroscopic alteration such as blue or red shift in emission.…”
Section: Discussionmentioning
confidence: 99%